2019
DOI: 10.2196/12081
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Low Glycemic Index Diet Consultations Through a Diet Glycemic Assessment App Tool on Maternal and Neonatal Insulin Resistance: A Randomized Controlled Trial

Abstract: Background Low glycemic index (LGI) diet has shown to be effective in reducing maternal and neonatal complications in high-risk pregnancies. Objective This trial aimed to examine the effectiveness of individualized LGI diet consultations based on the accurate diet glycemic load (GL) assessment tool on maternal and neonatal insulin resistance levels and diet behavior changes in overweight and obese pregnant women. Methods Overweight and obese … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Over the decades, microbiological studies proposed that intestinal flora could cause diabetes by regulating lipid metabolism to increase energy storage ( 12 ), producing short-chain fatty acids to mediate the release of intestinal hormones ( 13 ), and regulating bile acid metabolism to influence intestinal barrier function ( 14 ). Imbalance of intestinal flora has great influences on the host metabolism which eventually lead to occur and develop diabetes under a certain diet habit ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the decades, microbiological studies proposed that intestinal flora could cause diabetes by regulating lipid metabolism to increase energy storage ( 12 ), producing short-chain fatty acids to mediate the release of intestinal hormones ( 13 ), and regulating bile acid metabolism to influence intestinal barrier function ( 14 ). Imbalance of intestinal flora has great influences on the host metabolism which eventually lead to occur and develop diabetes under a certain diet habit ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study was a secondary data analysis using a historical cohort (ClinicalTrials.gov registry: NCT01628835). Details of the previous study design, recruitment, methods and responses could be found elsewhere ( 14 ). Briefly, overweight or obese gravidae [BMI ≥24 kg/m 2 according to national consensus of BMI cut-off for Chinese adults ( 15 )] aged 20–45 years old were recruited at first antenatal visit ≤ 14 gestational weeks in two hospitals [Kunshan Maternity and Child Care Center (Kunshan city, Jiangsu province, China) and the International Peace Maternity and Child Health Hospital of China Welfare Institute (Shanghai, China)] from June 2012 to October 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Five studies recruited women in their first trimester with a BMI ≥ 25 kg/m 2 . [28][29][30][31][32] Mean participant BMI for these studies ranged between 28.0 and 34.4 kg/m 2 , which was reported pre-pregnancy 28,31 or from first-trimester body weight. 29,30,32 In the DALI study women were selected with a pre-pregnancy BMI ≥ 29 kg/m 2 , 33 and UPBEAT study, participants had a pre-pregnancy BMI ≥ 30 kg/m 2 .…”
Section: Study Selectionmentioning
confidence: 97%
“…28,33 The UPBEAT study involved eight weekly health-trainer led sessions on reducing dietary GL without restricting dietary energy intake. 34,35 Compliance checks in addition to study visits were food diaries 39,40 or 24-h food recall, 28,39,41 telephone interviews, 30,31,[33][34][35] and a logbook with weekly goals in one study. 34,35 Comparison group Most studies described control groups as receiving usual care that included standard periodic antenatal visits and referral for medical care as indicated (i.e.…”
Section: Intervention Deliverymentioning
confidence: 99%
See 1 more Smart Citation